Sebaceous neoplasms with rippled, labyrinthine/sinusoidal, petaloid, and carcinoid-like patterns: a study of 57 cases validating their occurrence as a morphological spectrum and showing no significant association with muir-torre syndrome or dna mismatch repair protein deficiency - Wiedemeyer, Katharina; Kyrpychova, Liubov; Isikci, Özlem Tanas; Spagnolo, Dominic V.; Kutzner, Heinz; Rütten, Arno; Fernandez-Figueras, Maria T.; Denisjuk, Natalja; Suster, Saul; Pavlovsky, Michal; Petersson, Fredrik; Michal, Michal; et al. (The American journal of dermatopathology, 2018)
Sebaceous neoplasms with an organoid pattern (rippled, labyrinthine/sinusoidal, carcinoid-like, and petaloid) are rare. Previous studies suggested that the above patterns likely represent variations along a morphological continuum. The objectives of this study were to (1) validate this proposition by studying a large number of cases, (2) determine whether there are specific associations with clinical features, (3) establish their frequency, and (4) determine whether they have any association with Muir-Torre syndrome.